2017
DOI: 10.1177/0047287517729758
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Memorable Food, Drink, and Culinary Tourism Experiences

Abstract: This study identified elements leading to memorable food, drink, or culinary experiences while traveling. More than 1,000 respondents in four countries described their most memorable food or drink travel experience. Qualitative analysis found five general elements leading to memorable food travel experiences: food or drink consumed, location/setting, companions, the occasion, and touristic elements (e.g., novelty, authenticity). While these elements were frequently mentioned together, a single element (e.g., e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
190
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 214 publications
(258 citation statements)
references
References 45 publications
(77 reference statements)
18
190
1
5
Order By: Relevance
“…The significance of food uniqueness is also confirmed by the findings of previous studies (Goolaup & Mossberg, ; Guan, ; Kauppinen‐Räisänen et al, ). Similarly, the importance of food tradition is supported by studies on local food tourism (Jiménez‐Beltrán et al, ; Stone & Migacz, ), whereas the importance of service quality is supported by the findings of other researchers (Ab Karim & Chi, ; Choe & Kim, ; Stone et al, ).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…The significance of food uniqueness is also confirmed by the findings of previous studies (Goolaup & Mossberg, ; Guan, ; Kauppinen‐Räisänen et al, ). Similarly, the importance of food tradition is supported by studies on local food tourism (Jiménez‐Beltrán et al, ; Stone & Migacz, ), whereas the importance of service quality is supported by the findings of other researchers (Ab Karim & Chi, ; Choe & Kim, ; Stone et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…A review of local food tourism literature suggests that local food attributes can be summarized as falling into the categories of food quality, tradition, uniqueness, and service quality (Chi, Chua, Othman, & Karim, ; Kim & Choe, ; Kim & Eves, ; Verbeke & Poquiviqui López, ). Previous studies have consistently shown that positive perceptions of the quality of local food positively effects future intentions (Adongo, Anuga, & Dayour, ; Chi et al, ; Horng, Liu, Chou, & Tsai, ; Jiménez‐Beltrán, López‐Guzmán, & González Santa Cruz, ; Kim, Choe, & Lee, ; Kim & Eves, ; Mynttinen, Logrén, Särkkä‐Tirkkonen, & Rautiainen, ; Stone et al, ). A study by Kim and Eves () found that the sensory appeal of local food is a significant factor leading to its consumption in tourist destinations.…”
Section: Local Food Gastronomy and Its Effects On Intentions For Recomentioning
confidence: 97%
See 3 more Smart Citations